1995
DOI: 10.1126/science.7667636
|View full text |Cite
|
Sign up to set email alerts
|

CDC25 Phosphatases as Potential Human Oncogenes

Abstract: Cyclin-dependent kinases (CDKs) are activated by CDC25 phosphatases, which remove inhibitory phosphate from tyrosine and threonine residues. In human cells, CDC25 proteins are encoded by a multigene family, consisting of CDC25A, CDC25B, and CDC25C. In rodent cells, human CDC25A or CDC25B but not CDC25C phosphatases cooperate with either Ha-RASG12V or loss of RB1 in oncogenic focus formation. Such transformants were highly aneuploid, grew in soft agar, and formed high-grade tumors in nude mice. Overexpression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
347
1
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 476 publications
(357 citation statements)
references
References 43 publications
6
347
1
1
Order By: Relevance
“…This oncogenic activity of cyclin E is most interesting in the light of recent reports that implicate the deregulation of cyclin E in human cancer particularly breast carcinoma (Keyomarsi et al, 1995;Kitahara et al, 1995) and strongly suggest a direct role of aberrant cyclin E expression in the formation of a number of human malignancies that bear ampli®ed cyclin E genes. With this activity of cyclin E and recent ®ndings that ascribe a similar oncogenic potential to CDK4 (Haas et al, 1997) and CDC25 (Galaktionov et al, 1995) as well as the similar already known activity of D-type cyclins strongly suggest that all genes encoding positive G1 cell cycle regulators are in general protooncogenes and that their deregulated expression leads to a loss of growth control that is incremental in the process of malignant transformation. Moreover, this ®nding strengthens the relevance of restriction point control within the G1 phase of the cell cycle with regard to carcinogenesis (Bartek et al, 1996).…”
Section: Discussionmentioning
confidence: 64%
“…This oncogenic activity of cyclin E is most interesting in the light of recent reports that implicate the deregulation of cyclin E in human cancer particularly breast carcinoma (Keyomarsi et al, 1995;Kitahara et al, 1995) and strongly suggest a direct role of aberrant cyclin E expression in the formation of a number of human malignancies that bear ampli®ed cyclin E genes. With this activity of cyclin E and recent ®ndings that ascribe a similar oncogenic potential to CDK4 (Haas et al, 1997) and CDC25 (Galaktionov et al, 1995) as well as the similar already known activity of D-type cyclins strongly suggest that all genes encoding positive G1 cell cycle regulators are in general protooncogenes and that their deregulated expression leads to a loss of growth control that is incremental in the process of malignant transformation. Moreover, this ®nding strengthens the relevance of restriction point control within the G1 phase of the cell cycle with regard to carcinogenesis (Bartek et al, 1996).…”
Section: Discussionmentioning
confidence: 64%
“…These molecular alterations in adenoma PC/AA/C1 cells include the src and ras oncogenes, deficiencies in the APC tumor suppressor/b-catenin pathways, and induction of the active forms of the Cdc25 protein phosphatases by TFF1 in the present study. In agreement, Cdc25A and Cdc25B but not Cdc25C cooperate with activated Ras and loss of the pRb1 retinoblastoma tumor suppressor to transform primary rodent cells (Galaktionov et al, 1995). Validation of this model can be explored in transgenic animals harboring selectively these oncogenic alterations, in cooperation with forced expression of TFF1 in intestinal stem cells, through intestinal promoters that are functional in this cellular compartment, such as the villin (pVIL) and carcinoembryonic antigen (pCEA) regulatory regions.…”
Section: Discussionmentioning
confidence: 89%
“…In colorectal cancer patients, overexpression of Cdc25B protein phosphatase is a marker of poor prognosis (Takemasa et al, 2000). The nuclear phosphatases Cdc25A and B are potential oncogenic proteins associated with cell proliferation, foci formation, hypergrowth activity, and control of the G2/M checkpoint in response to DNA damage (Galaktionov et al, 1995;Daga and Jimenez, 1999;Xu et al, 2003;Boutros et al, 2006). The biological rationale of our results is further sustained by the induction of TFF1 in inflammatory hyperplastic polyps, premalignant and early stages of colon cancer, as shown here by RT-PCR, immunohistochemistry, and previously by immunoblot analysis (Emami et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to this study, we have shown that deregulated expression of cmyc blocks IL-6 induced terminal di erentiation of M1 cells, giving rise to cells which are blocked at an intermediate stage of di erentiation and continue to proliferate (Ho man-Liebermann and Liebermann, 1991a). The ®nding that cdc25A is an oncogene (Galaktionov et al, 1995;Parsons, 1998) as well as a c-myc target gene (Galaktionov et al, 1996), prompted us to study its expression in terminally di erentiating cells to assess whether cdc25A may mediate the c-myc induced block in M1 terminal di erentiation. To accomplish this, M1cdc25A cell lines with deregulated cdc25A expression were established.…”
mentioning
confidence: 99%